Lecturer Monitoring Information System in Providing Documents at the Faculty of Engineering University of Muhammadiyah Cirebon - Wicaksono, Freddy; Ardiansyah, Dimas; Isa Martinus, Agust (Ann Publisher, 2023)
The availability of document in an agency, both government and private, is important, because document contain information that can support all forms of activity in the agency. The availability of document at special higher education institutions of the faculty of engineering does not escape the role of lecturer, as people who play a role in preparing or preparing the necessary document for certain task. However, in its implementation, lecturer are sometimes often late in providing the necessary document, so that this can hinder ongoing activity. Therefore, in this study, the author created an information system to be able to monitor lecturers in providing documents. Users of this system are system administrators, deans, heads of study programs and lecturers. Based on the test results, the lecturer monitoring information system in providing documents can carry out assignment activities for lecturers, collection of assignment documents by lecturers and monitoring processes during the lecturer concerned in the assignment. With the lecturer monitoring application in providing document, the engineering faculty can monitor lecturer who have or have not collected document. The system also provides convenience for lecturer in monitoring the status of document that have been collected, whether they have been followed up or not by the faculty.